2017
DOI: 10.1523/jneurosci.3481-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Controls the Long-Term Survival and Phenotype of Repair Schwann Cells during Nerve Regeneration

Abstract: After nerve injury, Schwann cells convert to a phenotype specialized to promote repair. But during the slow process of axonal regrowth, these repair Schwann cells gradually lose their regeneration-supportive features and eventually die. Although this is a key reason for the frequent regeneration failures in humans, the transcriptional mechanisms that control long-term survival and phenotype of repair cells have not been studied, and the molecular signaling underlying their decline is obscure. We show, in mice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 75 publications
0
98
0
Order By: Relevance
“…We speculate the normal demethylation of H3K27, at least in young mice, may be sufficient to drive expression of adequate amounts of critical nerve repair genes. However, the ultrastructural analysis revealed that the function of Schwann cell EED is critical for timely axon regeneration, a function likely to be critical for efficient nerve regeneration since the survival and capacity of Schwann cells decrease at more distal sites that are chronically denervated (Benito et al 2017; Eggers et al 2010; Höke et al 2002; Jessen and Mirsky 1999; Jonsson et al 2013; Li et al 1997; Michalski et al 2008; Ronchi et al 2017; Sulaiman and Gordon 2009). …”
Section: Discussionmentioning
confidence: 99%
“…We speculate the normal demethylation of H3K27, at least in young mice, may be sufficient to drive expression of adequate amounts of critical nerve repair genes. However, the ultrastructural analysis revealed that the function of Schwann cell EED is critical for timely axon regeneration, a function likely to be critical for efficient nerve regeneration since the survival and capacity of Schwann cells decrease at more distal sites that are chronically denervated (Benito et al 2017; Eggers et al 2010; Höke et al 2002; Jessen and Mirsky 1999; Jonsson et al 2013; Li et al 1997; Michalski et al 2008; Ronchi et al 2017; Sulaiman and Gordon 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The first known transcription factor with this function is STAT3. This protein is not required for the initial generation of repair Schwann cells, but during chronic denervation, STAT3 is important both for the long‐term survival of these cells and for promoting the expression of c‐Jun and other repair program genes (Benito et al, ).…”
Section: Adaptive Cellular Reprogrammingmentioning
confidence: 99%
“…Similarly, developmental myelination is not controlled by the chromatin cross talk that in repair cells promotes silencing of myelin genes and activation of injury genes, and involves H3K27 demethylation coupled with H3K27 acetylation and H3K4 methylation (Hung et al, ; reviewed Ma & Svaren, ). STAT3 likewise is not involved in Schwann cell development although this factor is important for long‐term repair cell maintenance (Benito et al, ). Furthermore, the proliferation of adult Schwann cells that is triggered by injury and associated with the generation of repair cells requires cyclin D1, although this protein is not involved in the proliferation of developing Schwan cells (Kim et al, ).…”
Section: Adaptive Cellular Reprogrammingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we show that supernatant of ESWT‐treated Schwann cell cultures is significantly more potent in inducing neurites in vitro. This could be explained by an increased and prolonged induction of c‐jun and subsequent secretion of neurotrophic factor production, as other groups have shown that c‐jun activation results in a strong induction of pro‐regenerative genes …”
Section: Discussionmentioning
confidence: 97%